Stochastic controllability of linear systems with state delays - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
A class of finite-dimensional stationary dynamic control systems described by linear stochastic ordinary differential state equations with a single point delay in the state variables is considered. Using a theorem and methods adopted directly from deterministic controllability problems, necessary and sufficient conditions for various kinds of stochastic relative controllability are formulated and proved.
Keywords: controllability; linear control systems; stochastic control systems; delayed state variables; minimum energy control